PENGARUH PENGETAHUAN POLA HIDUP BERSIH DAN SEHAT (PHBS) TERHADAP SIKAP PHBS DI MASA PANDEMI COVID-19 DAN PENERAPAN PROTOKOL KESEHATAN DI KEC. MANGGALA KOTA MAKASSAR - Nurhasmi Nurhasmi; Herlinda Mahdania Harun; Asnaeni Ansar (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2023)
One of the risk factors that can affect public health problems is public hygiene. People in Manggala District are generally at risk of disease, especially Covid-19 infection. This situation must be prevented to reduce the adverse effects that can occur. This service aims to improve a healthy lifestyle, including the prevention of Covid-19 infection in the Manggala District. A total of 39 people attended this counseling. The counseling method used is by providing education about clean and healthy lifestyles (PHBS) and role-playing. This counseling is one of the recommended programs to encourage the formation of a healthy environment.